If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -9 + 5x = -9 Add '9' to each side of the equation. -9 + 9 + 5x = -9 + 9 Combine like terms: -9 + 9 = 0 0 + 5x = -9 + 9 5x = -9 + 9 Combine like terms: -9 + 9 = 0 5x = 0 Solving 5x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Divide each side by '5'. x = 0 Simplifying x = 0
| 7x+5=7-7x | | 6x+12=-28-4c | | 7x^2+6=17x-5 | | 6x+9+7y-2x+3= | | 8+6x=-22+x | | 4x-8+3x=60-2x+3x | | t*4-4=11 | | P^2=5p+84 | | 10y-3=8y+7 | | x+88+127=180 | | 3-2(2-x)=8 | | x+88=127 | | 88+127=x | | 2x+3(x+3)=x+3 | | 3.02+d=2.91 | | 4n+8n= | | 13000.00+25000x=27500x | | x+66=117 | | 3x^2+48x-300=0 | | .12x+x=273.16 | | 4(x-3)+4=21 | | 12212n=-48 | | 6x+17=24-3x | | a^5+5=15 | | 2x+y=270 | | 0=-4sin(2x) | | 4n+6=27-3n | | lx-9l=18 | | 8x^2-2x=-1 | | 2x+9x-8x=13+2 | | (5h-6)=x^2-5x-3 | | (4x-6)(8-x)=0 |